Bus Ticket System for Public Transport Using QR Code. (October 2019) - Upendra Reddy, C.; Vara Prasad Reddy, D.L.S.; Srinivasan, N.; Albert Mayan, J
Abstract: In this paper, we are proposing QR reader for a bus ticket. Users can scan QR reader instead of the ticket. In this app, after registration profile, we have to attach our bank details to this app and add money to the wallet. Whenever we go by bus, we have to select from and to location. Then it will generate amount details for per head. Also, we can buy a ticket for extra members and produces the mean count. It Scans the QR code from the conductor of the bus with a particular ID. Then we can scan QR code. So directly money will transfer from our wallet to transport corporation on basis of conductor ID. Then we will get an SMS alert for ticket payment proof. The admin side (Transport Corporation), they calculate amount details of a particular conductor through using web application. Then they can calculate per day amount details of Transport Corporation for buses.